2013
DOI: 10.1111/jhn.12060
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed eating behaviours and associated psychographic characteristics of college students

Abstract: Background: Young adulthood is a stressful transition period that may increase the risk for disturbed eating, especially for college students. The present study aimed to explore disturbed eating behaviours and a broad array of associated psychographic characteristics in a large, diverse sample of college students. Methods: College students (n = 2604; 58% white; 63% female) enrolled at three large, public US universities in 2009 and 2010 were recruited to take an online survey. The survey included reliable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 61 publications
2
60
1
8
Order By: Relevance
“…Background Disordered eating represents an over focus on body shape and weight reflecting in conditions marked by abnormal and disrupted attitudes to food and patterns of eating [1,2]. Evidence suggests that adolescence and early adulthood are the most vulnerable times to develop disordered eating patterns and predominantly those affected are young women aged 15-25 years [3][4][5].…”
Section: Review Article Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Background Disordered eating represents an over focus on body shape and weight reflecting in conditions marked by abnormal and disrupted attitudes to food and patterns of eating [1,2]. Evidence suggests that adolescence and early adulthood are the most vulnerable times to develop disordered eating patterns and predominantly those affected are young women aged 15-25 years [3][4][5].…”
Section: Review Article Open Accessmentioning
confidence: 99%
“…The first year as an undergraduate university student can be significantly stressful [2,[10][11][12]. We also know that stress may contribute to, or trigger patterns of disordered eating [4,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating disorders are the common psychiatric illnesses with a persistent disturbance in eating patterns or other behaviors intended to control weight, body size or shape. (1) Eating disorders also affect physical and nutritional health, psychological functioning and if untreated, they can be fatal. (2) Earlier studies have shown that eating disorders have the highest mortality rate of any mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from late adolescence to early adulthood is a critical time for adopting inadequate eating patterns 15 . Consequently, they have a high frequency of eating disorders, particularly those involving compulsive behaviors 16 . In addition, some of the syndrome components are common among college students.…”
mentioning
confidence: 99%